Retinal regions shape human and murine Muller cell proteome profile and functionality - Kaplan, Lew; Drexler, Corinne; Pfaller, Anna M.; Brenna, Santra; Wunderlich, Kirsten A.; Dimitracopoulos, Andrea; Merl-Pham, Juliane; Perez, Maria-Theresa; Schlötzer-Schrehardt, Ursula; Enzmann, Volker; Samardzija, Marijana; Puig, Berta; et al. (Glia, 2022)
The human macula is a highly specialized retinal region with pit-like morphology and rich in cones. How Muller cells, the principal glial cell type in the retina, are adapted to this environment is still poorly understood. We compared proteomic data from cone- and rod-rich retinae from human and mice and identified different expression profiles of cone- and rod-associated Muller cells that converged on pathways representing extracellular matrix and cell adhesion. In particular, epiplakin (EPPK1), which is thought to play a role in intermediate filament organization, was highly expressed in macular Muller cells. Furthermore, EPPK1 knockout in a human Muller cell-derived cell line led to a decrease in traction forces as well as to changes in cell size, shape, and filopodia characteristics. We here identified EPPK1 as a central molecular player in the region-specific architecture of the human retina, which likely enables specific functions under the immense mechanical loads in vivo.
CRIS-Team WoS Importer:2022-11-25